1997
DOI: 10.3354/meps151091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sediment-associated phenanthrene on survival, development and reproduction of two species of meiobenthic copepods

Abstract: The lethal and sublethal toxlclty of phendnthrene (a polycyclic aromatic hydrocarbon, PAH) to 2 species of meiobenthic estuarine harpacticoid copepods (Schfzopera knabeni dnd Nitocra lacustrfs) was ~nvestlgated Individuals of different life stages ( n a u p l~u s copepodite, adult male and female) were exposed to sediment-associated phenanthrene In separate 10 d bioassays Overall A' lacustns (10 d LCj, values ranglng from 43 to 105 pg g ' d~y wt) was more sensitive than S knabeni (10 d LCSD values ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Lotufo (1997Lotufo ( , 1998 after exposing 2 meiobenthic copepod species to sediment-associated fluoranthene over 10 and 14 d, respectively, found that sublethal effects on feeding and impairments of embryonic development occurred at lower concentrations than those causing adult mortality. Lotufo & Fleeger (1997) studying toxic effects of sediment-associated phenanthrene on different life-stages of meiobenthic copepods also reported higher sensitivities for naupliar stages.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lotufo (1997Lotufo ( , 1998 after exposing 2 meiobenthic copepod species to sediment-associated fluoranthene over 10 and 14 d, respectively, found that sublethal effects on feeding and impairments of embryonic development occurred at lower concentrations than those causing adult mortality. Lotufo & Fleeger (1997) studying toxic effects of sediment-associated phenanthrene on different life-stages of meiobenthic copepods also reported higher sensitivities for naupliar stages.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, meiobenthic copepods were exposed to aqueous and foodassociated fluoranthene, cypermethrin and deltamethrin. Fluoranthene is a polycyclic aromatic hydrocarbon (PAH) that is a common contaminant in many coastal systems, usually associated with discharge of petroleum and atmospheric depositions of combustion by-products (Kenish 1992, Lotufo & Fleeger 1997, Lotufo 1998. Insecticide pyrethroids such as cypermethrin and deltamethrin occur in marine coastal areas usually associated with agricultural runoff (Chandler et al 1994).…”
Section: Abstract: Life-history Effects · Fluoranthene · Cypermethrimentioning
confidence: 99%
“…Of additional concern, adult S. knabeni, such as those used in the present bioassays, are very tolerant of phenanthrene compared to earlier life history stages. For example, significant effects of phenanthrene on reproductive output were detected at concentrations as low as 22 mg/kg dry sediment [45]. Therefore, if Cd-phenanthrene combinations exert a strong synergistic effect on reproduction in S. knabeni, effects would be expected to occur at much lower concentrations than for adult lethality.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic toxicity assays in juveniles showed however that survival, growth and reproduction were all negatively affected by the added perylene. Lotufo and Fleeger (1997) also found negative effects of sub-lethal concentrations of PAH on the reproduction of meiobenthic estuarine copepods, mostly due to decreased rate of brood production and impairment of hatching.…”
Section: Ncmentioning
confidence: 92%